2023
DOI: 10.3390/ijms24109010
|View full text |Cite
|
Sign up to set email alerts
|

Candidate SNP Markers Significantly Altering the Affinity of TATA-Binding Protein for the Promoters of Human Hub Genes for Atherogenesis, Atherosclerosis and Atheroprotection

Abstract: Atherosclerosis is a systemic disease in which focal lesions in arteries promote the build-up of lipoproteins and cholesterol they are transporting. The development of atheroma (atherogenesis) narrows blood vessels, reduces the blood supply and leads to cardiovascular diseases. According to the World Health Organization (WHO), cardiovascular diseases are the leading cause of death, which has been especially boosted since the COVID-19 pandemic. There is a variety of contributors to atherosclerosis, including li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 226 publications
0
2
0
Order By: Relevance
“…This comparison was made to analyze whether these genes are under the influence of natural selection or neutral drift. We found that natural selection acts against underexpression of hub genes for atherogenesis, atherosclerosis and atheroprotection and, through enhanced atheroprotection, contributes to improved human health (Bogomolov et al, 2023).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…This comparison was made to analyze whether these genes are under the influence of natural selection or neutral drift. We found that natural selection acts against underexpression of hub genes for atherogenesis, atherosclerosis and atheroprotection and, through enhanced atheroprotection, contributes to improved human health (Bogomolov et al, 2023).…”
mentioning
confidence: 94%
“…Considering that to date quite a lot of studies have already been conducted in which this kind of annotation has been carried out, we will present the work (Bogomolov et al, 2023) as an example using the Human_SNP_TATAdb database for annotation and identification of candidate SNP markers of atherogenesis, atherosclerosis and atheroprotection.…”
mentioning
confidence: 99%